SPRAY NOZZLES PERFORMANCE IN FUNGICIDES APPLICATIONS FOR ASIAN SOYBEAN RUST CONTROL - Durão,Cléber França (2017)
ABSTRACT: The performance of fungicides in controlling Asian soybean rust depends, in part, the spray quality of these products. The market of components to spray offers new types of nozzles which generate droplets with different characteristics. This study aimed to verify whether applications of fungicides with different spray nozzles interfere in soybean rust control. The experiment was conducted in the 2013/2014 harvest. The experimental design was a randomized block with three replications, and compared ten spray nozzles and a control without fungicide application. The applications were made with a backpack sprayer pressurized with CO2, set to apply a spray volume of 150 L ha-1. For the determination of severity four plants per plot were sampled, quantifying in each leaflet the number of uredinia cm-2, which permitted to integrate the area under the disease progress curve (AUDPC). We concluded that HYPRO GUARDIAN® 120015 Single pre orifice flat spray nozzle, that generates medium size of droplets, provided the lowest AUDPC of soybean rust, as well as the use of fungicide reflected in grain yield, which was on average 288% higher than that obtained by the control without fungicide application.